HSCT FOR AUTOIMMUNE DISEASES - Oliveira, Maria Carolina; Ruiz, Milton Artur; Moraes, Daniela; Dias, Juliana Elias; Piron-Ruiz, Lilian; Ribeiro, Andreza Feitosa; Rodrigues, Morgani; Hamerschlak, Nelson (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
THE BRAZILIAN SOCIETY FOR BLOOD AND MARROW TRANSPLANTATION (SBTMO) PRESENTS THE BRAZILIAN GUIDELINES ON HEMATOPOIETIC STEM CELL TRANSPLANTATION